Potential of solar water disinfection (SODIS) for pathogen control during water scarcity crisis - Alotaibi, Mohammad; Al-Khalaifah, Hanan (Frontiers in Water, 2026)
Solar water disinfection (SODIS) is an emerging, sustainable method for improving water quality in regions facing limited access to safe drinking water, including the Middle East and North Africa (MENA). SODIS has been applied to a wide range of microorganisms, which show varying levels of sensitivity to the treatment. Dormant forms, such as spores and cysts, are typically more resistant to inactivation, while bacteria are, in general, more susceptible and can be inactivated within 1 h, depending on solar irradiance intensity. The higher the solar radiation, the faster the inactivation process. Virus inactivation by SODIS follows a pattern similar to that of bacteria, although MS2 bacteriophage is more resistant than both bacteria and other viruses. While some microorganisms require extended exposure times (up to 6 h), certain additives or methods can significantly reduce the time needed for effective disinfection. For example, hydrogen peroxide (H2O2), which forms via reactive oxygen pathways, acts as an oxidative agent, damaging DNA and contributing to the inactivation process. Singlet oxygen (1O2), a key reactive species, is responsible for oxidizing proteins and breaking down DNA and RNA strands, leading to microbial cell death. Overall, SODIS is an effective, low-cost, and simple method for pathogen inactivation, requiring minimal skills and equipment, making it particularly useful in disaster-stricken areas such as those affected by earthquakes or other natural disasters. Its accessibility and effectiveness make it particularly valuable in disaster-stricken areas and resource-limited settings, providing a practical strategy for reducing waterborne disease risks in the MENA region.